Effect of double-diffusion processes in the deep ocean on the distribution and dynamics of particulate and dissolved matter: a case study in the Tyrrhenian Sea - Xavier Durrieu de Madron; Paul Blin; Mireille Pujo-Pay; Vincent Taillandier; Pascal Conan (Ocean Science, 2025)
This study examines conductivity–temperature–depth (CTD), acoustic Doppler current profiler (ADCP) and optical data collected during the PERLE-3 cruise in March 2020 between the surface and 2000 m depth over an east–west section of the Tyrrhenian Sea in the Mediterranean. The focus is on the impact of double-diffusion processes, in particular salt fingering, on the distribution and dynamics of particulate and dissolved matter. Staircases form at the interface between the warm, saline Eastern Intermediate Water (EIW) and the colder, less saline Tyrrhenian Deep Water (TDW) in the centre of the basin in a region of weak hydrodynamic activity. The results show that thermohaline staircases formed by salt fingering significantly influence particle sedimentation and biogeochemical cycling in deep ocean environments by altering vertical flux patterns. These density steps create distinct vertical layers that act as physical barriers, slowing the descent of particles and facilitating their retention and aggregation. The retention of fine particles at density gradients promotes the formation of larger aggregates, thereby affecting the particle size distribution. The staircases also affect dissolved matter by creating pronounced concentration gradients of oxygen and nutrients, which may influence microbial activity and nutrient fluxes.